Brazilian competition law and access to health in Brazil: Exploitative pricing in the pharmaceutical sector - Bruno Braz de Castro (South Centre, 2022)
This paper aims to analyze the interfaces between Brazilian Competition Law and the issue of access to medicines, with a special focus on abuse of industrial property rights and related exclusionary and exploitative effects. The paper analyzes the case law of Brazilian Administrative Council for Economic Defense (CADE) in the pharmaceutical sector and discusses abusive practices such as illegitimately imposing non-existent or invalid intellectual property rights with anticompetitive purposes. It then addresses abusive strategies in the exercise of industrial property rights which are, in essence, valid: i.e., exclusionary practices, aimed at artificially raising barriers to entry; and exploitative practices, directly translated as the exercise of market power to the detriment of the consumer. The latter ultimately result in exploitative excessive prices; contractual, quality or privacy degradation; and restrictions on supply, such as by hoarding/preventing the exploitation of industrial property rights. The paper concludes that the prohibition of exploitative pricing under the current competition law is legally valid and effective, with certain methodological concerns towards reducing the risk of wrongful convictions (for instance, by applying screening tests to determine the markets that are candidates for intervention). In view of such guidelines, the pharmaceutical industry appears to be an important candidate for antitrust attention, given the magnitude of the harm potentially derived from non-intervention against the practice. Remedies in this area, importantly, should focus on identifying and solving the sector's structural competitive problems. In the case of medicines subject to price regulation by the Drug Market Regulation Chamber (CMED), the technical expertise of the competition authority may be of great value in terms of competition advocacy, a fact that is demonstrated in light of recent discussions on extraordinary price adjustments because of competitive problems in certain markets.
Keywords: 300; Access to Healthcare; Access to Medicines; Antitrust; Brazil; Competition; Competition Law; Competition Policy; Competition Regulation; COVID-19; Health; Industrial Property; Industrial Property Rights; Intellectual Property; Intellectual Property Rights (IPRs); Pandemic; Pharmaceuticals